Synthesis of Learning on CGIAR's Ways of Working - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2025)
This synthesis of learning on CGIAR’s Ways of Working (WoWs), prepared under the System Council–endorsed Multi-Year Evaluation Plan (MYEP), brings together evidence on all WoWs featured in the CGIAR 2030 Research and Innovation Strategy, which outlines how CGIAR aims to work differently. These include: